EVALUASI PENYELENGGARAAN PROGRAM SEKOLAH MENENGAH ATAS NEGERI BINAAN KHUSUS KOTA DUMAI - Wawan Setyawan; Isjoni Isjoni; Azhar Azhar (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2022)
This research has the purpose to know the implementation of Binaan Khusus Public Senior High School Of Dumai City. Research is focused on (1) Program to improve the quality of teachers and education personnel of Binaan Khusus Public Senior High School Of Dumai City, (2) Standard improvement program for facilities and infrastructure of Binaan Khusus Public High School Of Dumai City, (3) Student coaching program of Binaan Khusus Public Senior High School Of Dumai City. The theory that is used to evaluate Binaan Khusus Public Senior High School Of Dumai City programs is the theory put forward by Stufflebeam is the CIPP (Context, Input, Process dan Product) model theory. The research conducted is descriptive using a qualitative approach. A qualitative descriptive approach is used to describe the research findings as they are. Data collection was done by documentation, interviews, and observations. The research findings are presented in the form of interview transcripts supported by observations and documentation. This is done by triangulation steps, member checks, and peer examination. The research results show that : (1) Binaan Khusus Public Senior High School Of Dumai City has made an effort to improve the quality of teachers ad education personnel, (2) Binaan Khusus Public Senior High School Of Dumai City is already made effort to improve the standard of facilities and infrastructure, and (3) Binaan Khusus Public Senior High School Of Dumai City have carried out the maximum coaching of students.